EVALUASI PROGRAM PELATIHAN MANAGEMENT TRAINEE STUDI KASUS: SHARIA BANKER DEVELOPMENT PROGRAM (SBDP) NANOBANK SYARIAH 2025 - Handayani, Eliis; Kartika, Lindawati (PT Naureen Digital Education, 2025)
The competency gap between graduates and industry needs in Indonesia, driven by low education and labor efficiency, underscores the need to evaluate training program sustainability. This study assesses the Sharia Banker Development Program (SBDP) Nano Bank Syariah 2025 by identifying participant characteristics, evaluating training effectiveness using the Kirkpatrick model, and calculating the Return on Training Investment (ROTI). Employing a mixed-methods approach with 38 purposively selected respondents, data were analyzed descriptively using NVivo 15 and visualized via SIPOC diagrams. Results reveal 88% participant satisfaction, an average post-test score of 92, and a 76% action learning project outcome, indicating enhanced knowledge and skills. Additionally, 52% of participants expressed interest in financial sector careers, with a Net Promoter Score of 12%. A 136% ROTI confirms program viability. Recommendations include post-training mentoring, structuring content from foundational to technical, and expanding technical training duration and topics.